PRODUCTION AND CHARACTERIZATION OF BIODIESEL-DIESEL BLENDS FROM Terminalia Catappa SEED OIL - Sani, L.; Ajibola, V. O.; Abechi, S. E. (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigates the opportunity of using Terminalia catappa seed oil as a renewable and alternative fuel source. The oil was extracted using mechanical pressing and solvent extraction method and the percentage oil yield was 56.30%. The oil was degummed using 4% Citric acid and the physiochemical properties of the oil were carried out using standard methods. The acid value, viscosity, moisture content and ash content were found to be 3.82 mgKOH/g, 46.0 mm2/s, 2.40 % and 0.65 %w/w respectively. Biodiesel was produce via a two stage esterification and transesterification. Fuel properties of biodiesel produced were carried out using American Standard for Testing and Material (ASTM) methods Biodieseldiesel blend of B6, B10, and B20 were prepared and the influence of blending on fuel properties was determined. Result showed that biodiesel and blend of B6-B20 satisfy ASTM D6751 and ASTM D7467 standards, respectively.